Application of BIM+GIS in Water Resources Allocation Project of the Pearl River Delta - DU Canyang; DENG Peng; ZHANG Zhaobo; ZHU Xiaobin (Renmin Zhujiang)
The water resources allocation projects in the Pearl River Delta are characterized by multiple points,long lines,complex technology,long construction periods,and difficult coordination. On this basis,new information technologies such as BIM,GIS,electronic signature,cloud computing,big data,Internet of Things (IoT),artificial intelligence (AI),and mobile Internet are applied to build a whole-life-cycle BIM+GIS system platform by integrated innovation and collaborative sharing. It incorporates an information-based standard system,a resource pool for engineering big data,a BIM+GIS support platform,a system for electronic signature applications,a multi-information awareness and early warning platform with visual analysis,and a situation-assisted decision application based on a BIM+GIS project panorama.The whole-life-cycle BIM+GIS system platform serves all the participating units including industry supervision and the construction,design,supervision,and safety monitoring of engineering.The digitization,information,and intelligence levels of engineering construction management have reached internationally advanced levels.